Effects of dutasteride in a rat model of chemically induced prostatic inflammation—Potential role of estrogen receptor β. Issue 16 (17th September 2020) - Mizoguchi, Shinsuke; Mori, Kenichi; Shin, Toshitaka; Wang, Zhou; DeFranco, Donald B.; Yoshimura, Naoki; Mimata, Hiromitsu
Abstract: Background: Dutasteride administration reportedly improves lower urinary tract symptoms in patient with chronic, histologically‐identified prostatic inflammation, potentially through estrogen receptor β (ERβ), activation of which has anti‐inflammatory effects in the prostate tissue. Therefore, we investigated the effect of dutasteride on intraprostatic inflammatory responses and bladder activity using a rat model of chemically induced prostatic inflammation. Methods: Male Sprague–Dawley rats at 10 weeks old were used. Prostatic inflammation was induced by 5% formalin injection into ventral lobes of the prostate and saline was injected in the control group (control, n = 5). Rats with prostatic inflammation were divided into dutasteride therapy (dutasteride, n = 5) and placebo groups (placebo, n = 5). Dutasteride was administrated at a dose of 0.5 mg/kg daily from 2 days before induction of prostatic inflammation whereas placebo rats received vehicle only. Twenty‐eight days later, cystometry was performed in a conscious condition to measure non‐voiding contractions (NVCs), intercontraction intervals (ICI) and postvoid residual volume (RV). After cystometry, the prostate was excised for analysis of messenger RNA (mRNA) expression levels of ERα, ERβ, interleukin‐1β (IL‐1β), and IL‐18 by quantitative polymerase chain reaction. Results: The mean number of NVCs was significantly greater in placebo group than that of control group without prostatic inflammation ( p < .05), and ICI were significantly decreased in placebo group compared with control group ( p < .05). On the contrary, there was no significant change in NVCs or ICI between control and dutasteride groups. RV was not significantly different among three groups. Gene expression levels of ERα, IL‐1β, and IL‐18 was significantly increased in placebo rats compared with control rats ( p < .05), but not significantly different between control and dutasteride rats. On the other hand, the mRNA expression level of ERβ was significantly decreased in placebo rats ( p < .05), but not in dutasteride rats, compared with control rats. Conclusion: Dutasteride treatment improved not only prostatic inflammation evident as increased gene expression levels in IL‐1β and IL‐18, but also bladder overactivity shown by increased NVCs during bladder filling. These therapeutic effects were associated with the restored expression of anti‐inflammatory ERβ. Therefore, dutasteride might be effective via ERβ modulation for the treatment of prostatic inflammation in addition to its previously known, anti‐androgenic effects on benign prostatic hyperplasia.